2019
DOI: 10.23910/ijbsm/2019.10.6.2041
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Pod Borers on Pigeonpea (Cajanus cajan (L) Millsp.) in Relation to Abiotic Factors

Abstract: Pigeonpea (Cajanus cajan (L) Millspaugh) is a tropical grain legume mainly grown in India and ranks second in area and production and contribute about 90% in the world's pulse production. In India pigeonpea was grown in 3.96 mha with a production of 2.56 mt and productivity of 646 kg ha-1 , whereas, in Andhra Pradesh, India the area, production, productivity of pigeonpea was 0.22 mha, 0.13 mt and 600 kg ha-1 , respectively during 2015-16 (Anonymous, 2017). Though the area under redgram is increasing, the yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The present results are corroborating with the results of Mallikarjuna et al (2012), who reported that the population density of M. vitrata in Lablab purpureus (L.) Sweet reached its peak from the first week of December (48 th SMW). Similarly, in pigeon pea [Cajanus cajan (L.)], Sreekanth et al (2015) and Sreekanth et al (2019) reported that the larval population per plant increased from 47 th SMW and reached its peak during the end of December (12.6 larvae/plant at 51 st SMW). Like the Summer season, the larval abundance gradually declined and reached 3.20 larvae in flowers and 4.60 larvae in pods.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The present results are corroborating with the results of Mallikarjuna et al (2012), who reported that the population density of M. vitrata in Lablab purpureus (L.) Sweet reached its peak from the first week of December (48 th SMW). Similarly, in pigeon pea [Cajanus cajan (L.)], Sreekanth et al (2015) and Sreekanth et al (2019) reported that the larval population per plant increased from 47 th SMW and reached its peak during the end of December (12.6 larvae/plant at 51 st SMW). Like the Summer season, the larval abundance gradually declined and reached 3.20 larvae in flowers and 4.60 larvae in pods.…”
Section: Resultsmentioning
confidence: 94%
“…Even though there was ample information available in India on the M. vitrata seasonal abundance, infestation and impact of weather parameters on major pulses, pigeon pea (Sharma et al, 1999;Sreekanth et al, 2015;Sreekanth et al, 2019;Taggar et al, 2019;Sujayanand et al, 2021) and black gram (Swamy and Devaki, 2015;Kapoor, 2019), the data is inadequate concerning Dolichos bean (Lablab purpureus var. typicus).…”
Section: Resultsmentioning
confidence: 99%
“…Insect pests are the major constraints resulting in this low productivity, with about 18 insect pests (Jayasinghe et al, 2015;Khan et al, 2018). Notably, the lepidopterans feeding on the flowers and pods of food legumes cause significant yield losses (Rouf and Sardar, 2011;Sreekanth et al, 2019;Tagger et al, 2019;Sujayanand et al, 2021). Amongst this M. vitrata (Lepidoptera: Crambidae) is a serious legume pest with high damage potential and a wider host range (Jackai 1995;Sharma 1999;Margam et al, 2011;and Periasamy et al, 2015).…”
mentioning
confidence: 99%